Cognitive, personality, and social factors associated with adolescents' online personal information disclosure - Lwin, May Oo (2013)
The current study aims to understand the factors that influence adolescents' disclosure of personally identifiable information (PII) on social networking sites (SNSs). A survey was conducted among 780 adolescent participants (between 13 and 18) who were Facebook users. Structural equation modeling was used for analyzing the data and obtaining an overarching model that include cognitive, personality, and social factors that influence adolescents' PII disclosure. Results showed privacy concern as the cognitive factor reduces adolescents' PII disclosure and it serves as a potential mediator for personality and social factors. Amongst personality factors, narcissism was found to directly increase PII disclosure, and social anxiety indirectly decreases PII disclosure by increasing privacy concern. Amongst social factors, active parental mediation decreases PII disclosure directly and indirectly by increasing privacy concern. Restrictive parental mediation decreases PII disclosure only indirectly by increasing privacy concern. Implications of the findings to parents, educators, and policy makers were discussed.